Uji potensi pertumbuhan beberapa varietas tanaman jagung (Zea mays) di Kabupaten Bireuen - Nazirah, Laila; Zuhra, Intan; Satriawan, Halus (Universitas Muhammadiyah Mataram, 2022)
The corn plant is one of the most important food crops other than rice and soybeans. Besides being consumed as direct food and animal feed, it is also used as raw material for other industries, such as alternative fuels, polymers, corn oil and others. This study aims to determine maize varieties that have high growth potential and yields in Bireuen District. This research was conducted from September 2020 to January 2021 in the village of Cot Kruet Makmur Subdistri, Bireuen District, Aceh Province. This study used a randomized completely block design (RCBD) consisting of 7 varietas of corn plant, namely the Bonanza variety, Royal 76 variety, Talenta Variety, Ganebo variety, Sweet Boy variety, Paragon variety, Jambore variety. The observed parameters consist of a growth component and a yield component. Growth components include: plant height, number of leaves, stem diameter, and 50% flowering age. While the yield components included: weight of corn cob, length of corn with cob, number of seeds per cob, weight of cob seeds, weight of 1000 grains, and yield per hectare. The result showed that the adaptation test of several varieties of corn plant had a different effect on each observation. Jambore variety is one of the varieties tested for its adaptation in this study, this variety has great potential to be developed in Bireuen district, because the Jambore variety is able to produce the most cobbled cob result among other varieties, weighing is about 22,84 ton ha-1.